2009
DOI: 10.5465/amj.2009.41330897
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects Of Organizational And Professional Identification On The Reciprocity Dynamic For Professional Employees

Abstract: We consider when professional employees reciprocate perceived organizational treatment. In a large sample of physician employees, the association between perceived organizational support (POS) and employee work performance was (1) most positive when organizational identification was high and professional identification was low and (2) least positive when organizational identification was low and professional identification was high. We also found that the association between perceived psychological contract vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
187
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(203 citation statements)
references
References 99 publications
(133 reference statements)
6
187
2
8
Order By: Relevance
“…Em segundo lugar, as análises de consistência interna, por dimensão, revelaram-se próximas do valor identificado pelos autores (Armeli, Eisenberger, Fasolo, & Lynch, 1998;Eisenberger, Huntington, Hutchison, & Sowa, 1986), e por estudos subsequentes (Hekman, Steensma, Bigley, & Herefors, 2009), podendo assim considerar-se fidedignas as medidas fornecidas pela versão portuguesa.…”
Section: Discussão E Conclusãounclassified
“…Em segundo lugar, as análises de consistência interna, por dimensão, revelaram-se próximas do valor identificado pelos autores (Armeli, Eisenberger, Fasolo, & Lynch, 1998;Eisenberger, Huntington, Hutchison, & Sowa, 1986), e por estudos subsequentes (Hekman, Steensma, Bigley, & Herefors, 2009), podendo assim considerar-se fidedignas as medidas fornecidas pela versão portuguesa.…”
Section: Discussão E Conclusãounclassified
“…O"Neill Olivia (2009) identified that low level of perceived organizational support yields anger in employees and results in absenteeism, job accidents, inventory loss, alcohol consumption and turnover. Hekman et al (2009) "Perceived Organizational Support had the most positive influence on employees' work performance when employees strongly identified with the organization and weakly identified with the profession". When employees are actively identified with the organization rather than their profession.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…According to Hekman, Steensma, Bigley, & Hereford, (2009), perceived Organizational Support puts highly positive impact over employees" job performance. Concept of organizational support was introduced by an American expert in psychology and behavioral sciences, Eizenberger in 1986.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…For organizational scholars, organizational identification has been used as a way to assess the extent to which an individual feels at one with the organization. It has been shown in research on physicians that a strong organizational identification relates positively to performance (Hekman, Bigley, Steensma and Hereford, 2009). This literature has explored how individuals identify with organizations, teams and professions.…”
Section: Gendered Identification: Broadening the Concept Of Role Modelsmentioning
confidence: 99%